2016
DOI: 10.1039/c6cp01744d
|View full text |Cite
|
Sign up to set email alerts
|

The ionic transport mechanism and coupling between the ion conduction and segmental relaxation processes of PEO20-LiCF3SO3 based ion conducting polymer clay composites

Abstract: A series of ion conducting polymer-clay composites has been prepared using a solution casting technique. Relaxation dynamics and the ionic transport mechanism are systematically studied employing broadband dielectric spectroscopy over a wide frequency and temperature range. Among different phenomenological and theoretical models for ion conduction in disordered ionic conductors, conductivity isotherm spectra are analysed using the modified Almond-West and random free energy barrier model. Conductivity scaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Numerous studies have shown that polymer chain groups in composite structures can be more easily orientated by thermal excitation due to the applied field effect, [28][29][30][31][32][33][34] suggesting that in LLDPE-PE-g-MA/clay nanocomposite, DC conductivity has a significant contribution in the low frequency region due to ionic motion while it is not the case in LLDPE-OxPE/clay nanocomposite. 35 The peaks in both samples observed to shift towards high frequency indicate that the clay was not homogeneously dispersed in the structure due to the effect of the compatibilizer (OxPE) and that different polarization mech-anisms were formed, confirming the results of the study conducted by Durmuş et al on the structural characterization of LLDPE-OxPE/clay composites. 20,21 Figures 7, 8 and 9 show the temperature-dependent changes in the dielectric constant of pure LLDPE, LLDPE-PE-g-MA/ clay and LLDPE-OxPE/clay nanocomposites, respectively, in the frequency range of 10 -1 -10 6 Hz.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Numerous studies have shown that polymer chain groups in composite structures can be more easily orientated by thermal excitation due to the applied field effect, [28][29][30][31][32][33][34] suggesting that in LLDPE-PE-g-MA/clay nanocomposite, DC conductivity has a significant contribution in the low frequency region due to ionic motion while it is not the case in LLDPE-OxPE/clay nanocomposite. 35 The peaks in both samples observed to shift towards high frequency indicate that the clay was not homogeneously dispersed in the structure due to the effect of the compatibilizer (OxPE) and that different polarization mech-anisms were formed, confirming the results of the study conducted by Durmuş et al on the structural characterization of LLDPE-OxPE/clay composites. 20,21 Figures 7, 8 and 9 show the temperature-dependent changes in the dielectric constant of pure LLDPE, LLDPE-PE-g-MA/ clay and LLDPE-OxPE/clay nanocomposites, respectively, in the frequency range of 10 -1 -10 6 Hz.…”
Section: Resultssupporting
confidence: 82%
“…Moreover, the proportional arrangement of charges in question indicates a pronounced polarization between surfaces. 29,32,[34][35][36] The shift of dielectric losses to the high frequency region with an increase in temperature suggests that the conductivity of LLDPE-PE-g-MA/clay nanocomposite is somewhat higher than that of the others.…”
Section: 폴리머 제42권 제5호 2018년mentioning
confidence: 99%
“…The latter relaxation is ascribed to local mobility [45]. It can also be observed that the M'' spectra are asymmetric when the temperature increases and skewed towards for higher frequencies for all the doped samples, suggesting fast ionic motion [47].…”
Section: Thermal and Mechanical Analysismentioning
confidence: 76%
“…The relaxation time τ 2 depends on the process of charge accumulation on the electrode polarization. For the high-frequency behavior of the ac conductivity, the modified Almond–West formalism was used with the following equation where σ dc , ω c , n , and m are the dc conductivity, a crossover frequency, and a power law exponent, respectively; the parameter A is weakly dependent on temperature. Based on eqs and , the complex conductivity in the whole frequency region can be expressed as …”
Section: Resultsmentioning
confidence: 99%